Man a machine - La Mettrie, Julien Offray de, 1709-1751.; Bussey, Gertrude Carman, 1888-1961.; Calkins, Mary Whiton, 1863-1930; Frederick II, King of Prussia, 1712-1786. (Chicago, The Open court Pub. Co., 1912)
Including Frederick the Great's "Eulogy" on La Mettrie's "The Natural History of the Soul"
Frederic the Great's Eulogy on Julien Offray De La Mettrie 1 -- L'Homme Machine 11 -- Man a Machine 83 -- The Natural History of the Soul: Extracts 151 -- La Mettrie's Relation to His Predecessors and to His Successors 165 -- Outline of La Mettrie's Metaphysical Doctrine 175.
"The French text presented in this volume is taken from that of a Leyden edition of 1748 ... The title page of this edition is reproduced in the present volume."--Pref.
The translation is founded on a version made by Miss Gertrude C. Bussey (from the French text in the edition of J. Assezat) and has been revised by Professor M.W. Calkins, who is responsible for it in its present form. cf. Pref.
"Works consulted and cited in the notes": p. [205]-207.
"Works consulted and cited in the notes": p. [205]-207.
Keywords: Physiology -- Early works to 1800.; Materialism; Mind and body